Analytical Characterization and Inhibitor Detection in Liquid Phases Obtained After Steam Refining of Corn Stover and Maize Silage - Krafft, Malte Jörn; Berger, Jens; Saake, Bodo (Frontiers in Chemistry, 2021)
The utilization of agricultural products and residues for the production of value-added and biobased products is a highly relevant topic in present research. Due to the natural recalcitrance of lignocellulosic biomass against enzymatic degradation, pretreatments are important requirement for further processes. For the raw material in this study, corn stover (CS) as highly available agricultural residue and maize silage (MS) as model substrate for an ensiled agricultural product were pretreated by steam refining. However, after this process there are different fractions e.g., fibers and a liquid fraction. The fiber fraction after steaming processes is well characterized. Nonetheless, in depth characterizations of the filtrates are also important for their subsequent utilization. Decreasing molar masses from 7900 g/mol to 1100 g/mol for CS filtrates and 100.000 g/mol to 12.900 g/mol for MS filtrates were determined with an increase of the severity. Weak acids, furans and phenolic compounds were analyzed in the liquid phase due to the knowledge of their inhibitory effect on microorganisms. Especially formic acid increases with increasing severity from 0.27% to 1.20% based on raw material for CS and from 0.07% to 0.23% based on raw material for MS. Further GC/MS measurements show, that up to 8.25% of the total peak area is related to inhibitory phenols in CS filtrates and 5.23% in MS filtrates. With that in mind, detoxification strategies are also important for filtrates after steam refining and should be considered for further research and process or parameter optimizations. An alternative may be the application of milder process conditions in order to prevent the formation of inhibitory degradation products or the dilution of the gained filtrates.